Polylactide Nanocapsules Attenuate Adverse Cardiac Cellular Effects of Lyso-7, a Pan-PPAR Agonist/Anti-Inflammatory New Thiazolidinedione - Giani M. Garcia; Jérôme Roy; Ivan R. Pitta; Dulcinéia S. P. Abdalla; Andrea Grabe-Guimarães; Vanessa C. F. Mosqueira; Sylvain Richard (MDPI AG, 2021)
Lyso-7 is a novel synthetic thiazolidinedione, which is a receptor (pan) agonist of PPAR α,β/δ,γ with anti-inflammatory activity. We investigated the cardiotoxicity of free Lyso-7 in vitro (4.5-450 nM), and Lyso-7 loaded in polylactic acid nanocapsules (NC) in vivo (Lyso-7-NC, 1.6 mg/kg). In previous work, we characterized Lyso-7-NC. We administered intravenously Lyso-7, Lyso-7-NC, control, and blank-NC once a day for seven days in mice. We assessed cell contraction and intracellular Ca2+ transients on single mice cardiomyocytes enzymatically isolated. Lyso-7 reduced cell contraction and accelerated relaxation while lowering diastolic Ca2+ and reducing Ca2+ transient amplitude. Lyso-7 also promoted abnormal ectopic diastolic Ca2+ events, which isoproterenol dramatically enhanced. Incorporation of Lyso-7 in NC attenuated drug effects on cell contraction and prevented its impact on relaxation, diastolic Ca2+, Ca2+ transient amplitude, Ca2+ transient decay kinetics, and promotion of diastolic Ca2+ events. Acute effects of Lyso-7 on cardiomyocytes in vitro at high concentrations (450 nM) were globally similar to those observed after repeated administration in vivo. In conclusion, we show evidence for off-target effects of Lyso-7, seen during acute exposure of cardiomyocytes to high concentrations and after repeated treatment in mice. Nano-encapsulation of Lyso-7 in polymeric NC attenuated the unwanted effects, particularly ectopic Ca2+ events known to support life-threatening arrhythmias favored by stress or exercise.